Contemporary management of complex craniofacial trauma: virtual planning, navigation and the novel thermoformed cage splints in a strategic, sequential, computer-guided protocol. Issue 11 (November 2022) - Tel, Alessandro; Costa, Fabio; Sembronio, Salvatore; Robiony, Massimo
Abstract: Introduction: It was the aim of the study to assess if computerized simulation and the use of thermoformed cage splints are useful to plan cases of complex craniofacial trauma. Materials and methods: patients with fractures in any of the thirds of the craniofacial skeleton and occlusion impairment. Virtual surgical planning with digital reduction of fractures, navigated planning, thermoformed cage splints were used in all cases. Surgical outcomes were evaluated by computing the surface deviation and occlusograms between planned and postoperative models. Results: 13 patients were enrolled in this study. Accuracy of bone repositioning was evaluated compared with the surgical planning. For the mandible, mean Root Mean Square Error (RMSE) was of 1.67 with a standard deviation (SD) of ±0.75 mm (p < 0.001); for the maxilla, average RMSE was of 0.88 with SD of ±0.52 mm (p < 0.001); and for midfacial and upper third bone segments, average RMSE was of 0.59 with SD of ±0.47 mm (p < 0.001) Conclusions: Within the limitations of the study it seems that thermoformed cage splints might be a promising alternative to other well-established approaches for accurate occlusal restoration and can be fully integrated within the digital workflow.